Alteridade e literatura: compreensões sobre a proposta antropofágica oswaldiana - MELO, Arlen Maia de (2020)
The present work has as objective to analyze the prominence of the thematic of the alterity and it is unfolding in the work O Manifesto Anthropófago (1928), by Oswald de Andrade. For this purpose, this general objective is developed in specificities, namely: the need to recognize how the relation of this other / prisoner to the figure of the wild subject is configured; understand the notion of alterity and the anthropophagic proposal in the Brazilian modernist literature; reflect on the legacy left by the modernist studies of Oswald de Andrade and how they are consolidated in a current resignification of the cannibal man. The method used for the development of this work consists of a bibliographic study. This work uses the works of Candido (1997), Fausto (2011), Kiening (2014), Nunes (1979) among other scholars. The modernist contribution of Oswald de Andrade and his production in the Brazilian literary scene are important and significant for the recognition of the national identity. With this, the propagation of the true "anthropophagous man" collaborates with the thinking of a Brazil of the new, modern, and even, authentic. A country constituted by difference, but often it was, and still is, marked by the constant denial of this "other."